Land cover change in Himalaya with special reference to forest disturbance: A case of Bharse area, Lesser Himalaya, West Central Nepal - Gautam, Chinta Mani; Watanabe, Teiji (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.138-9